RANCANG BANGUN SISTEM INFORMASI PENDATAAN DAN MONITORING TUMBUH KEMBANG ANAK SEBAGAI UPAYA PENCEGAHAN STUNTING DESA KOTAPARI - Muttaqin, Muhammad; Rizki Ananda Pratama (CV. Hawari, 2022)
Stunting is one of the problems being faced by Kotapari Village. The absence of an information system about stunting that is easily accessible to the public is one of the aspects that has slowed down the resolution of the stunting problem. To accelerate the resolution of the stunting problem, it is considered necessary to have an information system that can help the community easily and quickly. Methods of data collection is done by interviews and observation. In this study the system development method used is waterfall with the supporting software used are PHP and MySQL. Seeing the reality above, it is deemed necessary to build a website-based information system that is useful to facilitate Kotapari Village and the Community in working to resolve the stunting problem in Serdang Bedagai Regency. Apart from being able to provide stunting information to the community, this application also has a child health check menu related to child growth and a discussion menu that can be used by the community to communicate with Kotapari Village.